Persepsi Mahasiswa terhadap Dosen dalam Mengajar di Fakultas llmu Komunikasi Universitas Prof. Dr. Moestopo (Beragama) - Sunarto, Sunarto; Syahudi, Giman; Erland, Radja (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2008)
This research of background overshadow by existence of some problems of arisingout in course of study like for example less obedient the lecturer to discipline teach and less precisely instruction method used by some lecturer, this matter have opportunity to generate impact of student, by unfavourable ways of lecturer in teaching to generate ugly perception among student to lecturer,so that in the end will affect at degradation of education quality.Pursuant to the background hence problems which lifted in this research is " How perception Student to Lecturer of teaching in Faculty of Communications Science, Universityof Prof Dr. Moestopo (Beragama)?' To solve the problems of researcher use theory A. Devito Learning Education Processand of Persepsion Process, Theory Cognitive of DavidA. Aeker and theory of nature and also perception element from Sasa Djuarsa Sendjaja. As for Conceptualization of approach the theory is that things required to dug from perception of Student cover appearance of lecturer teach, compliance of lecturer to discipline teach, teach method, domination to lesson items and the also domination of class..